Counting 1 2 3 lift the flaps and count to 10 - Peto, Violet; Lewis, Liza (New York, New York DK Publishing, 2019)
"Count the animal eggs from 1 to 10. Can you guess what will hatch? Peek through the holes and flip the flaps to find out!"--Page 4 of cover
Arithmetic Notions
At head of title: Flip flap find!
Cover title
On board pages
Keywords: Board books; Animals; Board books; Counting; Eggs; Lift-the-flap books; Animals -- Juvenile literature; Board books; Counting -- Juvenile literature; Eggs -- Juvenile literature; Lift-the-flap books -- Specimens; Animals; Counting; Eggs; Lift-the-flap books; Toy and movable books; Board books